The First Year of the Priority 2030 Program Implementation: Positive Results and Problem Areas of Research Track Universities - A. I. Guseva; V. M. Kalashnik; V. I. Kaminsky; S. V. Kireev (Moscow Polytechnic University, 2023)
The article considers the results of the main activities of universities - participants' groups of the Priority 2030 program of the «Leadership in Research» track (hereinafter referred to as the research track) at the initial stage of its implementation. An analysis of performance indicators' dynamics for groups of universities in the period preceding the implementation of the program (2017-2020) and the first year of its implementation (2021) was carried out. Special attention is given to the analysis of the activities of universities that are leaders in the research track. As part of the comprehensive analysis, positive results were identified, as well as some problem areas in the activities of universities. An analysis of the basic indicators shows that the researched groups of universities in a number of indicators have a relatively small difference in the achieved values, while the indicators of the special part revealed an unconditional group of leaders.